Analisis Pertanggungjawaban Pidana Terhadap Pelaku Penipuan Perempuan yang Dijadikan Pekerja Seks Komersial - Intan Nurina Seftiniara (PRANATA HUKUM, 2015)
Trafficking in persons is a complex issue and involves many factors ( economic , social , and cultural ) . In order to combat the crime of human trafficking , Indonesia passed Law No. 21 of 2007 on the Eradication of Trafficking in Persons . The problem in this research are : a) . How is the criminal responsibility of the perpetrators of fraud women who were commercial sex workers ? b ) What is the basis for consideration of the judge in the case ruled against fraudulent women who were commercial sex workers ? Based on the results of research and discussion, the conclusion is obtained Against Perpetrators Criminal Fraud Accountability Women Who Used as commercial sex workers in the name of defendant Sunarti Als . Narti Bint Matnur and Fitria Als . Pipit Binti Sonny Rahman accountable , because the defendant is able to account for his actions , his actions deliberately and absence of an excuse . Basic consideration in the judge decide the case by looking at his actions , his mistakes , his ability is responsible , and the evidence in the trial are also conscience . Suggestions authors in this paper are: a) It should be nurtured awareness and understanding of the community 's good about the law in order to prevent further frauds which can be detrimental to the community , b) Should a judge must always maintain morality and personal integrity of the judge or conscience , in order to distinguish between good deeds and bad , in order to maintain the image of a judge .